The Impact of Religiosity, And Sustainability Awareness on Campus Impact Sustainability - Datu Razali Datu Eranza; Lee, Andy Chen Hiung (Universiti Malaysia Sabah, 2017)
This paper provides an insight on the impact of religiosity and sustainability awareness on the campus impact sustainability. The nature of this study was to explore the relationships and using the survey questionnaire for primary data collection. The research question for this research was Do religiosity and sustainability awareness affecting the campus impact sustainability? A Convenience sampling technique was applied to sample more than 150 students at the Faculty of Business, Economics, and Accountancy, in Universiti Malaysia Sabah (UMS). Adaptation of three different questionnaires were used to construct the questionnaire of this research. General measures of religiosity refer to its intensity, salience, and importance in the individuals, and mostly are self-report on single item on the subjective importance of religion or the salience of religious identity. For better measurement in religiosity, the authors have adopted the Centrality of Religiosity Scale (CRS) questionnaire developed by Stefan Huber and Odilo W. Huber. The Scale is a set of 15 items measurement on centrality, importance or salience of religious meanings in personality. Four questions were developed to measure the awareness and concern of students about the environmental sustainability. Third part of the questionnaire is a 26-items questionnaire by McNulty. Apart from it, the authors have also included several demographic factors to investigate whether the gender and parents education level would influence the variables.